Exogenous Testosterone and Estrogen Affect Bladder Tissue Contractility and Histomorphology Differently in Rat Ovariectomy Model - ERCAN, FERİHA; TARCAN, TUFAN; TANIDIR, YILÖREN (WILEY, 2011)
Introduction. Changes in sex hormone levels may play a role in the etiology of lower urinary tract dysfunction of aging women where the possible role of testosterone is overlooked. Aim. To determine the effect of testosterone with/without estrogen replacement on histological and functional deterioration in ovariectomized rat bladder tissue. Methods. A total of 54 female Sprague Dawley rats were divided into 6 groups. Except sham operated (control group), all others underwent bilateral ovariectomy. No further treatment was given to the ovariectomy-only group (OVX group). At the third week of ovariectomy treatments were started; vehicle agent (VA group), estradiol (E2 group), testosterone undecanoate (T group), and estradiol + testosterone undecanoate combination (E2 + T group) in physiological doses. Nine weeks after ovariectomy, bladder strips were harvested for isometric tension and histopathological studies. Main Outcome Measures. To assess the effect of testosterone/estradiol on ovariectomized rat bladder tissue function and histomorphology. Results. OVX and VA groups showed statistically significant histological changes such as urothelial damage, inflammatory cell infiltration, increase in collagen fibers and muscular atrophy compared with the control group. Both E2 and T reversed these changes but best histomorphological restoration was observed in E2 + T group. In isometric tension studies, ovariectomy tended to increase contractile responses which were normalized after E2 treatment. In contrary to E2, T significantly increased contractile responses that were normalized with combination treatment. During relaxation studies statistically significant higher relaxation responses were observed in ovariectomized rats. Although both exogenous testosterone and estradiol tended to reverse this effect, a statistically significant difference was found only after testosterone treatment. Conclusion. Either estradiol or testosterone replacement alone or in combination prevents significant alterations in bladder tissue histology following ovariectomy whereas both affect the bladder tissue contractility. Thus, combination treatment appears to be the best method to restore both contractility and histomorphology of bladder tissue after ovariectomy. Tanidir Y, Ercan F, and Tarcan T. Exogenous testosterone and estrogen affect bladder tissue contractility and histomorphology differently in rat ovariectomy model. J Sex Med 2011;8:1626-1637.
Keywords: Urinary Bladder; Ovariectomy; Estradiol; Testosterone; Menopause and Androgens; Smooth Muscle Contraction; Cell Morphology; ANDROGEN LEVELS; SMOOTH-MUSCLE; ESTRADIOL; REPLACEMENT; MENOPAUSE